Encapsulation of Fe3O4 with amina modified silica - Roswanda, Robby; Mujahidin, Didin (Jurnal Keramik dan Gelas Indonesia, 2017)
Superparamagnet iron oxide Fe3O4 particles were encapsulated with amina modified silica via Stober Method. The particles generated were rod-like whose length was c.a. 2 Âµm and the thickness of silica shell was c.a. 75 nm. Magnetization measurements show that the silica shell does not disrupt the superparamagnetic property of Fe3O4. The amine group on the encapsulated particles was confirmed by attaching FITC (Fluorescein isothiocyanate) dye and checked under fluorescence microscope. The encapsulated particle is useful to be modified further for various applications that need magnetic field control.